Are sub-Saharan African Countries Losing it on Oil and Gas Revenue Management too? Evidence from Ghana - Ali-Nakyea, Abdallah; Amoh, John Kwaku; Mohammed, Nasir Alfa (International Journal of Energy Economics and Policy, 2019)
The judicious management of revenues from natural resources has been challenging. This paper examines the effectiveness of Revenue Management Laws for oil and gas revenues in Ghana. This is to assess whether Ghana has learnt any lessons from the challenges of mineral revenues management. The study found that the management of the minerals and mining sector revenues is disturbing and some imminent problems identified in the management of the recent oil and gas revenues. The study recommends the adoption of Drysdale's five principles of effective natural resource revenue management to avoid such problems associated with an influx of natural resource wealth. We recommend a consolidation of Petroleum Revenue Management Act, 2011 (Act 815) and the Petroleum Revenue Management (Amendment) Act, 2015 (Act 893) to provide consistency in interpreting the oil and gas Revenue Management Laws. We posit that with the experiences in the minerals and mining sector emphasized and the implementation of our recommendations, Ghana would be better informed on how to establish an effective and efficient framework to manage oil and gas revenues to spur Ghana Beyond Aid. Keywords: Ghana; mining; oil and gas; petroleum revenues; management; natural resources; mineral royalties; resource curse; minerals JEL Classifications: H2, Q2, Q3 DOI: https://doi.org/10.32479/ijeep.7285